The contribution role of personality-based typeface in reflecting a country’s identity / Mastura Mohd Jarit - Mohd Jarit, Mastura (Institute of Graduate Studies, UiTM, 2018)
The basic premise for this research was to investigate visual elements of the Malay Traditional Culture that infused in typography. The aim of this research was to ascertain the impact that an audience received and to get indepth knowledge for possible creative directions on the design of a typeface. Understanding the culture and traditions were the key elements in experimenting the idea of developing one’s typeface design. Once the appreciation of particular culture and traditions were realised, possible creative directions on the design and creation of typeface which derived from the visual elements of the Malays cuture. In order to design a quality and good typefaces, one need to focus on the concept, history, personality and traits of typefaces which then will characterized the identity and personality of the typeface. Many basic religious concept were introduced during the adoption of Islam in The Malay Peninsular. The Arabic scripts become so internalized within the Malay language. It was found that from the data analysis that Jawi characteristics were the base of concept and fundamental elements in the Malay culture. It has been a main contributing role of personality and it reflects the Malay identity.